Intangible Assets Disclosure and its Effect on Quality of Financial Reporting: Field Study on Jordanian Public Companies Listed on Amman Stock Exchange - Bani – Ateah, Naef; Bani – Ahmad, Audeh (The Arab Journal of Administration, 2022)
The study aims to investigate the effect of disclosing intangible assets on quality of financial reports. This is through conducting an empirical study among public shareholding Jordanian companies listed on the Amman Stock Exchange. To achieve the main objective of the study a questionnaire survey was developed, covering all study hypotheses. The study population consists of all 224 companies listed on the Amman Stock Exchange in 2017.The respondent of the current study includes financial managers, head of accounting departments and accountants in these companies. Questionnaires had been distributed among a sample of 50 companies, three questionnaires each, meaning that 150 questionnaires distributed in total. In a result, 122 questionnaires were returned and analyzed.The research design of the current study follows the descriptive and explanatory approach, using primary and secondary data sources. Regarding statistical analysis, T-test was implemented to test the first and second hypotheses of the study, while liner simple regression was used to test the third hypotheses. The study indicates the following results. Firstly, public shareholding Jordanian companies engage in disclosing intangible assets. Secondly, financial personnel in these companies have sufficient awareness and knowledge regarding disclosing intangibles in financial reports. Finally, results indicate a significant impact of disclosing intangibles on quality of financial reporting.